2020
DOI: 10.21203/rs.3.rs-42681/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age is not the only risk factor in COVID-19: the role of comorbidities and of long staying in residential care homes.

Abstract: Background: The actual SARS-CoV-2 outbreak caused a highly transmissible disease with a tremendous impact on elderly people. So far, few studies focused on very elderly patients (over 80 years old). In this study we examined the clinical presentation and the evolution of the disease in this group of patients, admitted to our Hospital in RomeMethods: This is a single-center, retrospective study performed in the Sant’Andrea University Hospital of Rome. We included patients older than 65 years of age with a diagn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It was found that most patients were 50 years of age or older. In keeping with this observation, it was evident that the elderly were more likely to contract COVID-19, compared to younger adults, and to progress to more severe disease with an unfavorable prognosis [19] . Animal model studies also demonstrated that viral replication of SARS coronavirus was enhanced in experimentally infected aged mice, compared to younger mice, and associated with alveolar damage, pneumonia, and clinical disease [20] .…”
Section: Discussionmentioning
confidence: 56%
“…It was found that most patients were 50 years of age or older. In keeping with this observation, it was evident that the elderly were more likely to contract COVID-19, compared to younger adults, and to progress to more severe disease with an unfavorable prognosis [19] . Animal model studies also demonstrated that viral replication of SARS coronavirus was enhanced in experimentally infected aged mice, compared to younger mice, and associated with alveolar damage, pneumonia, and clinical disease [20] .…”
Section: Discussionmentioning
confidence: 56%
“…From the very beginning of the oandemic, the risk of developing severe COVID-19 and the mortality rate have been associated with advanced age. Although the picture has been complicated since by the identification of numerous comorbidities [ 36 ], this holds still true. As a direct consequence, most countries have decided to start their vaccination programs against SARS-CoV-2 with the elderly, alongside the healthcare personnel and high-risk individuals [ 37 ].…”
Section: Spotlight On Original Articlesmentioning
confidence: 99%